Aesthetic coherence in omnichannel retail: visual arts and consumer engagement in Malaysia - Amer, Afizan; Ibrahim, Irwan; Selamat, Hayyum Suleikha; Ahmad Apandi, Anas Afandi; Sundram, Veera Pandiyan Kaliani (Faculty of Art and Design, 2025)
This study examines the strategic role of visual arts in bridging online and offline retail experiences within Malaysia’s dynamic and multicultural market. As omnichannel retailing becomes increasingly critical, retailers struggle to create cohesive consumer journeys across digital and physical touchpoints. Through qualitative semi-structured interviews with 20 participants (10 consumers and 10 retail professionals), this research explores how visual merchandising, digital art integration, and store ambiance influence consumer engagement, brand perception, and purchase intention. Thematic analysis reveals three key findings: (1) emotional engagement; consumers associate visually appealing stores with premium quality and prolonged dwell time; (2) tech-driven experiences; augmented reality (AR) and interactive displays enhance online-to-offline transitions when seamlessly integrated; and (3) cultural resonance; traditional motifs, when authentically adapted, strengthen connections with Malaysia’s diverse demographics. The study validates Aesthetic Theory (Berlyne, 1971) by demonstrating how visual stimuli shape emotional responses, while also advancing Omnichannel Retail Theory (Rigby, 2011) by highlighting the need for aesthetic consistency across platforms. Practical insights suggest that retailers should invest in unified visual branding, culturally sensitive designs, and phygital (physical + digital) storytelling to enhance consumer experiences. However, challenges such as internal silos between digital and in-store teams and the risk of superficial cultural appropriation must be addressed. This research contributes to retail marketing literature by empirically linking visual arts to consumer behavior in an emerging market context, offering actionable strategies for leveraging aesthetics as a competitive advantage. Future studies should quantify the ROI of visual merchandising and explore cross-cultural variations in aesthetic preferences.